An Analysis of the Impact of Human-Computer Interaction on Artificial Intelligence in Healthcare - Divyeshkumar, Vaghani (NeuroQuantology, 2024)
Human-computer systems (HCIs) interaction inspects how people develop, implement and utilize interactive computer systems and how computers affect people, organizations and society. Human-Computer Interaction (HCI) is a field that has been combining Artificial Intelligence and human-computer engagement over the past several years in order to create an interactive brilliant system for user interaction. This consists of not only ease of use but also new interaction tools that encourage user practices, enable access to data and make communication more effective. Knowledge is given and requested, how computer operations are handled and monitored and recorded, all forms of help, documentation and training, the techniques used to design, build, test and ascertain user interfaces and the process developers take when designing interfaces. Artificial intelligence (AI) is one of the emerging tools. In recent decades, artificial intelligence (AI) has gained widespread acceptance in a variety of fields, including virtual support, healthcare, and security. AI, in conjunction with HCI, is being used in a variety of fields by employing different algorithms and employing HCI to provide transparency to the user, allowing them to trust the machine. The inclusive examination of both the areas of AI and HCI, as well as their subfields, has been explored in this work. The main goal of this article was to discover a point of intersection between the two fields. The understanding of Artificial Intelligence (AI), which is a linking point of HCI and AI, was gained through a literature review conducted in this research. The literature covered themes identified in the study (such as AI and its areas, major AI aims, and AI challenges). The study's other major focus was on the use of AI and HCI. The poll also addressed the shortcomings in AI in healthcare, as well as the field's future potential. As a result, the literature indicates that AI is still a novel subject that has to be explored more in the future.